B cell-intrinsic epigenetic modulation of antibody responses by dietary fiber-derived short-chain fatty acids - Helia N. Sanchez (Nature Portfolio, 2020)
Dietary fiber-derived short-chain fatty acids (SCFA) act as histone deacetylase (HDAC) inhibitors on Tregs and innate immune cells, promoting immune tolerance by altering gene expression. Here the authors show that SCFA HDAC inhibitor activity impacts B cell differentiation, antibody responses and antibody-driven autoimmunity.